Hybrid Porous Silicon Biosensors Using Plasmonic and Fluorescent Nanomaterials: A Mini Review - Abu-Thabit, Nedal; Ratemi, Elaref (Frontiers in Chemistry, 2020)
During the last two decades, porous silicon (PSi) has been proposed as a high-performance biosensing platform due to its biocompatibility, surface tailorability and reproducibility. This review focuses on the recent developments and progress in the area related to hybrid PSi biosensors using plasmonic metal nanoparticles (MNPs), fluorescent quantum dots (QDs) or a combination of both MNPs and QDs for creating hybrid nanostructured architectures for ultrasensitive detection of biomolecules. The review discusses the mechanisms of sensitivity enhancement based on Localized Surface Plasmon Resonance (LSPR) of MNPs, Fluorescence Resonance Energy Transfer (FRET) in the case of MNPs/QDs donor-acceptor interactions, and photoluminescence/ fluorescence enhancement resulting from the embedded fluorescent QDs inside the PSi microcavity. The review highlights the key features of hybrid PSi/ MNPs/ QDs biosensors for dual-mode detection applications.